Preparation of ultrasmall cyclodextrin nanogels by an inverse emulsion method using a cationic surfactant. Issue 27 (20th March 2023) - Takeuchi, Satomi; Cesari, Andrea; Soma, Suzuka; Suzuki, Yota; Casulli, Maria Antonietta; Sato, Kai; Mancin, Fabrizio; Hashimoto, Takeshi; Hayashita, Takashi
Abstract : Ultrasmall cyclodextrin nanogels were prepared by an inverse emulsion method using a cationic surfactant. These nanogels provide a highly hydrophobic inner surface, allowing efficient solubilisation of hydrophobic compounds in water. Abstract : Stable water-in-oil emulsion membranes can be prepared using [dilauryl(dimethyl)ammonium] bromide (DDAB), a cationic surfactant. We prepared ultrasmall cyclodextrin (γ-CyD ) nanogels (γ-CyDngs ) by forming ionic pairs between the secondary hydroxyl groups of γ-CyDs and DDAB. Fluorescence and NMR characterisation of the obtained γ-CyDngs revealed superior inclusion affinities compared with native γ-CyDs, beneficial for the solubilisation of hydrophobic compounds in water.